Does eIF3 promote reinitiation after translation of short upstream ORFs also in mammalian cells?. Issue 12 (2nd December 2017) - Hronová, Vladislava; Mohammad, Mahabub Pasha; Wagner, Susan; Pánek, Josef; Gunišová, Stanislava; Zeman, Jakub; Poncová, Kristýna; Valášek, Leoš Shivaya
ABSTRACT: Reinitiation after translation of short upstream ORFs (uORFs) represents one of the means of regulation of gene expression on the mRNA-specific level in response to changing environmental conditions. Over the years it has been shown-mainly in budding yeast-that its efficiency depends on cis -acting features occurring in sequences flanking reinitiation-permissive uORFs, the nature of their coding sequences, as well as protein factors acting in trans . We earlier demonstrated that the first two uORFs from the reinitiation-regulated yeast GCN4 mRNA leader carry specific structural elements in their 5′ sequences that interact with the translation initiation factor eIF3 to prevent full ribosomal recycling post their translation. Actually, this interaction turned out to be instrumental in stabilizing the mRNA·40S post-termination complex, which is thus capable to eventually resume scanning and reinitiate on the next AUG start site downstream. Recently, we also provided important in vivo evidence strongly supporting the long-standing idea that to stimulate reinitiation, eIF3 has to remain bound to ribosomes elongating these uORFs until their stop codon has been reached. Here we examined the importance of eIF3 and sequences flanking uORF1 of the human functional homolog of yeast GCN4, ATF4, in stimulation of efficient reinitiation. We revealed that the molecular basis of the reinitiation mechanism is conserved between yeasts and humans.